Molecular-ion-imprinted chitosan hydrogels for the selective adsorption of silver(I) in aqueous solution - Song, X. (2013)
Chitosan hydrogels were prepared and imprinted by AgI with different mass ratios. Compared with the native chitosan hydrogel sample, the optimally imprinted sample (Agim75) presents a significantly enhanced AgI adsorption capacity as well as a high selectivity. This is attributed to the specific cavities formed by the template AgI ions in the polymer matrix. The effect of the adsorption conditions and desorption process were also studied.